A National “Struggle for Survival”? – The Badeni Crisis of 1897 in Cisleithania’s German-language Press - Victor Jaeschke (Sprawy Narodowościowe. Seria nowa, 2017)
A National “Struggle for Survival”? – The Badeni Crisis of 1897 in Cisleithania’s German-language Press